The Usages and Potential Uses of Alginate for Healthcare Applications - Mollah, M. Z. I.; Zahid, H. M.; Mahal, Z.; Faruque, Mohammad Rashed Iqbal; Khandaker, M. U. (Frontiers in Molecular Biosciences, 2021)
Due to their unique properties, alginate-based biomaterials have been extensively used to treat different diseases and in the regeneration of diverse organs. A lot of research have been done by the different scientific community to develop biofilms for fulfilling the need of sustainable human health. The aim of the review is to hit upon the hydrogel enhancing the scope of utilization in biomedical applications. The presence of active sites in alginate hydrogels can be manipulated for managing various non-communicable diseases by encapsulating with the bioactive component as a potential site for chemicals in developing drugs, macromolecule nutrients. Gels are accepted for cell implantation in tissue regeneration, as they can transfer cells to the expected site. Thus, the review will accelerate advanced research avenue in tissue engineering and their potentiality of alginate biofilm’s in the healthcare sector.